The trend of environmental and clinical methicillin-resistant Staphylococcus aureus in a hospital in Taiwan: Impact of USA300 - Chen-Hsin Yu (Journal of Microbiology, Immunology and Infection, 2022)
Background: The environment may facilitate transmission of health care-associated methicillin-resistant Staphylococcus aureus (MRSA) and the pathogen is frequently shed by patients. However, the molecular characteristics and genetic relatedness between clinical and environmental MRSA isolates remain largely unclear in the clinical setting. Methods: A total of 100 hospitalized patients with MRSA infection and 25 hospitalized patients without MRSA infection were enrolled in a medical center, Taiwan in 2019. Environmental and clinical MRSA isolates were characterized by antibiotic susceptibility testing and molecular methods. Results: In the study, we detected 17 MRSA isolates in the environment that surrounded 15 MRSA-infected patients and one environmental MRSA isolate from one patient without MRSA infection. The molecular analysis revealed a high genetic diversity within either environmental or clinical MRSA isolates, while the USA300 clone (pulsotype AI, SCCmec IV, ST8, PVL-positive) accounts for 39% (7/18) of environmental and 33% (7/21) of clinical MRSA isolates. Moreover, 13 of the 15 MRSA-infected patients had identical paired clinical-environmental MRSA isolates, which exhibited indistinguishable genetic relatedness and highly similar antibiotic susceptibility phenotype, suggesting a possible transmission cycle of MRSA in the hospital. Conclusions: The environmental MRSA was closely linked to MRSA isolated from patients, suggesting that the environment may act as a reservoir of MRSA. Besides, the USA300 MRSA has become a major clone in the hospital setting. An effective and rigorous approach to environmental cleaning and decontamination is suggested to eradicate MRSA in the hospital.